PUSAT PENGEMBANGAN KARIR UNIVERSITAS SIMALUNGUN JEMBATAN MERAIH PASAR KERJA - Mustafa Ginting; Kristianto Kristianto; Johan AS Silalahi (Universitas, 2021)
The Simalungun University Career Development Center, abbreviated as PPK USI, is one of the university level technical management units / institutions that was established on January 7, 2017, especially in the context of community service, namely:(1) Bridging students and alumnis both USI and non-USI with the business world, industry and government agencies that need workers, so that students and alumni more easily obtain information and services to enter the workforce, (2) Providing consulting services and career guidance for both USI and non-USI students and alumni in dealing with the world of work, and (3) Providing information on job vacancies and internships, conducting training on the world of work and entrepreneurship, and organizing the recruitment process for students and alumnis both USI and non-USI.The method of implementing service is carried out through science and technology diffusion, training and mediation. The services that PPK USI has achieved since its establishment are: (1) Disseminating career guidance, internship and work guidance information obtained directly from HRD and company leaders to the people who need it through social media such as Facebook, Twitter, Instagram, Linkedin and Line, (2) Organizing, Technical Guidance (Technical Guidance) such as briefing and try out selection of CAT-based CPNS, entrepreneurial talkshow for students in agriculture, training in digital marketing strategies, (3) Recruitment of labor through campus hiring and job fairs, (4) Carry out career guidance services in the form of training to make applications, make a good CV, practice interviews, and practice psychological testing, (5) Carry out student internships at The Government Company times a year.The activities that have been carried out are PPK USI work program, and all of them are public service activities.